Growing up in a megalopolis: environmental effects on galaxy evolution in a supercluster at z∼0.65 in UKIDSS UDS - Galametz, Audrey; Pentericci, Laura; Castellano, Marco; Mendel, Trevor; Hartley, Will G.; Fossati, Matteo; Finoguenov, Alexis; Almaini, Omar; Beifiori, Alessandra; Fontana, Adriano; Grazian, Andrea; Scodeggio, Marco; et al. (Oxford University Press, 2018)
We present a large-scale galaxy structure Cl J021734-0513 at z ∼ 0.65 discovered in the UKIDSS UDS field, made of ∼ 20 galaxy groups and clusters, spreading over 10 Mpc. We report on a VLT/VIMOS spectroscopic follow-up program that, combined with past spectroscopy, allowed us to confirm four galaxy clusters (M200 ∼ 1014 M⊙) and a dozen associated groups and star-forming galaxy overdensities. Two additional filamentary structures at z ∼ 0.62 and z ∼ 0.69 and foreground and background clusters at 0.6 < z < 0.7 were also confirmed along the line-of-sight. The structure subcomponents are at different formation stages. The clusters have a core dominated by passive galaxies and an established red sequence. The remaining structures are a mix of star-forming galaxy overdensities and forming groups. The presence of quiescent galaxies in the core of the latter shows that ‘preprocessing’ has already happened before the groups fall into their more massive neighbours. Our spectroscopy allows us to derive spectral index measurements e.g. emission/absorption line equivalent widths, strength of the 4000Å break, valuable to investigate the star formation history of structure members. Based on these line measurements, we select a population of ‘poststarburst’ galaxies. These galaxies are preferentially found within the virial radius of clusters, supporting a scenario in which their recent quenching could be prompted by gas stripping by the dense intracluster medium. We derive stellar age estimates using MCMC-based spectral fitting for quiescent galaxies and find a correlation between ages and colours/stellar masses which favours a top-down formation scenario of the red sequence. A catalogue of ∼ 650 redshifts in UDS will be released alongside the paper.